Toroidal, compression, and vortical dipole strengths in 144-154Sm: Skyrme-RPA exploration of the deformation effect - Kvasil, J.; Nesterenko, V. O.; Kleinig, W.; Bozik, D.; Reinhard, Paul-Gerhard; Lo Iudice, N. (European Physical Journal A, 2013)
A comparative analysis of toroidal, compressional and vortical dipole strengths in the spherical 144Sm and the deformed 154Sm is performed within the random-phase approximation using a set of different Skyrme forces. Isoscalar (T = 0), isovector (T = 1), and electromagnetic excitation channels are considered. The role of the nuclear convection jcon and magnetization jmag currents is inspected. It is shown that the deformation leads to an appreciable redistribution of the strengths and causes a spectacular deformation splitting (exceeding 5 MeV) of the isoscalar compressional mode. When stepping from 144Sm to 154Sm, we observe an increase of the toroidal, compression and vortical contributions in the low-energy region (often called pygmy resonance). The strength in this region seems to be an overlap of various excitation modes. The energy centroids of the strengths depend significantly on the isoscalar effective mass m0. Skyrme forces with a large m0 (typically m0/m ≈ 0.8-1) seem to be more suitable for the description of experimental data for the isoscalar giant dipole resonance. © Società Italiana di Fisica / Springer-Verlag 2013.
CRIS-Team Scopus Importer:2023-07-24